2019
DOI: 10.1101/720730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Design of Epitope Based Peptide Vaccine Against Pseudomonas Aeruginosa Fructose Bisphosphate Aldolase Protein using Immunoinformatics

Abstract: Pseudomonas aeruginosa is common pathogen that is responsible of serious illnesses hospital acquired infection as ventilator associated pneumonia and various sepsis syndrome. Also it is a multidrug resistant pathogen recognized for its ubiquity, its intrinsically advanced antibiotic resistant mechanisms. generally affects the immuonocompromised but can also infect the immunocompetent as in hot tub folliculitis. There is no vaccine against it available till now. This study predicts an effective epitope-based va… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Aldolase vaccination studies involving bacteria, fungi, or parasites all invariably resulted in the development of varying degrees of protection from challenge infection, and this was associated with induced cellular and/or humoral immune responses. Novel immunoinformatics approaches to predict optimal peptide sequences with strong binding affinities to host MHC molecules while minimizing allergic reactivity may prove useful in simplifying the search for specific antigenic epitopes within the enzyme structure ( Mohammed et al, 2018 ; Elhag et al, 2020 ). The development of new technologies such as immunoinformatics, the exploration of new vaccine designs and alternative routes of immunogen administration (i.e., protein versus DNA versus RNA, oral administration versus intramuscular etc.…”
Section: Discussionmentioning
confidence: 99%
“…Aldolase vaccination studies involving bacteria, fungi, or parasites all invariably resulted in the development of varying degrees of protection from challenge infection, and this was associated with induced cellular and/or humoral immune responses. Novel immunoinformatics approaches to predict optimal peptide sequences with strong binding affinities to host MHC molecules while minimizing allergic reactivity may prove useful in simplifying the search for specific antigenic epitopes within the enzyme structure ( Mohammed et al, 2018 ; Elhag et al, 2020 ). The development of new technologies such as immunoinformatics, the exploration of new vaccine designs and alternative routes of immunogen administration (i.e., protein versus DNA versus RNA, oral administration versus intramuscular etc.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study conducted by de Klerk et al [79] showed that the Fba1 protein has the ability to provoke immune responses in human against M. mycetomatis [79]. Also, several recent publications have used the Fba1 protein as a strong antigenic target for predicting Band T-cell epitopes in order to design promising vaccines against fungal and bacterial pathogens such as M. mycetomatis, P. aeruginosa, L. monocytogenes, and S. mansoni by using in silico tools [80][81][82][83]. Hence, there are more studies to explore the fructose bisphosphate aldolase protein immunogenic role and the possibility to find common conserved epitopes for different organisms.…”
Section: Discussionmentioning
confidence: 99%